Progress report on new antiepileptic drugs: A summary of the Fifteenth Eilat Conference on New Antiepileptic Drugs and Devices (EILAT XV). I. Drugs in preclinical and early clinical development. (14th November 2020) - Bialer, Meir; Johannessen, Svein I.; Koepp, Matthias J.; Levy, René H.; Perucca, Emilio; Perucca, Piero; Tomson, Torbjörn; White, H. Steve
Abstract: Since 1992, the Eilat Conferences have provided a forum for all stakeholders in the epilepsy community to appraise the latest data on new antiepileptic drugs and emergency seizure treatments, including, in recent years, updates on progress with the development of novel monitoring and therapeutic devices. Because of the COVID‐19 pandemic, the Fifteenth Eilat Conference on New Antiepileptic Drugs and Devices (EILAT XV) was held as a fully virtual conference on July 27‐30, 2020 for the sessions on drugs and on August 3, 2020 for the sessions on devices, and was attended during the 5 days by >500 participants from 63 countries. This progress report summarizes key preclinical and initial (phase 1) clinical data on eight investigational treatments that are currently in early development, including 2‐deoxy‐D‐glucose, GAO‐3‐02, JNJ‐40411813, NBI‐921352, NTX‐001, sec ‐butylpropylacetamide, XEN1101, and XEN496. This report provides an overview of current scenarios in the area of treatment discovery and development. The information presented illustrates a variety of innovative strategies, including exploration of compounds with novel mechanisms of action, transplantation of interneurons into epileptogenic brain regions, and the targeting of rare, previously neglected syndromes.